The Effect of Mentoring Training and Capital Assistance on the Impact of the BIDARI Program of BAZNAS Riau on Mustahik in Kuantan Singingi Regency - Teddy Niswansyah; Alsar Andri; Fauzil Hasdi; Gio Vani Jefri; Zaky Al Fadli; Al Fikri Fauzi (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2026)
Research has been conducted to examine the effect of mentoring training and capital assistance on the impact of the BIDARI Program. The questionnaire was distributed to 14 program beneficiaries. The data were analyzed using multiple regression analysis, F test, t test, and R² test. In the multiple linear regression analysis, the equation obtained was Y = -0.818 − 0.290X₁ + 1.468X₂. The F value shows 15.890, indicating that Fcount > Ftable, where 15.890 > 3.98, with a significance level of 0.001 < 0.05. This means that mentoring training (X₁) and capital assistance (X₂) simultaneously have a significant effect on program impact (Y). The t value for mentoring training is -0.829, which is smaller than the t-table value (|-0.829| < 2.201) with a significance level of 0.424 > 0.05, indicating no significant partial effect. Meanwhile, the t value for capital assistance is 3.753, which is greater than the t-table value (3.753 > 2.201) with a significance level of 0.003 < 0.05, indicating a significant positive effect. Based on the partial test, capital assistance is more dominant in influencing program impact. The R² value of 0.743 indicates that 74.3% of the variation in program impact can be explained by mentoring training and capital assistance. These results show that capital assistance plays a more decisive role in determining the level of improvement in the impact of the BIDARI Program.